Seasonal variation of source contributions to atmospheric fine and coarse particles at suburban area in Istanbul, Turkey - Karaca, Ferhat; Alagha, Omar; Erturk, Ferruh; Yilmaz, Yusuf Ziya; Ozkara, Tuerkan (MARY ANN LIEBERT, INC, 2008)
Daily samples of fine (PM2.5) and coarse (PM2.5-10) particles were collected from July 2002 to July 2003 to provide a better understanding of the elemental concentration and source contribution to both PM fractions. Sampling location represents suburban part of Istanbul metropolitan city. Samples were collected on Teflon filters using a Dichotomous Sampler. Concentrations of Al, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, V, and Zn were measured by GFAAS, FAAS, and FAES techniques. Elemental variations of heating and nonheating seasons were discussed. Fossil fuel-related atmospheric metals dramatically increased during the heating season, while natural originated atmospheric metals increased during the nonheating season. Seasonal variations of source contributions were evaluated using factor analysis, which was separately applied to the collected fine and coarse particles data sets during heating and nonheating seasons (four data sets: PM2.5 heating, PM2.5 nonheating, PM2.5-10 heating, and PM2.5-10 nonheating). Significant seasonal differences in source contributions were observed. Four factor groups were extracted for PM2.5 dataset during the nonheating season, while five factor groups were extracted for all the other cases. Mineral dust transportation, traffic, and industry-related activities were classified as different factor groups in all the cases.
Keywords: statistical analysis; dichotomous sampler; PM2.5 and PM2.5-10 particles; heating and nonheating seasonal variation; air pollution; TRACE-ELEMENT CONCENTRATIONS; AIRBORNE PARTICULATE MATTER; DRY DEPOSITION FLUXES; CHEMICAL-COMPOSITION; METAL CONCENTRATIONS; AEROSOL; PM10; AIR; URBAN; PM2.5; Engineering; Environmental Sciences & Ecology